Suspended and substrate sediment sizes of the lower Rio Puerco, New Mexico - Milhous, Robert T., author; Fleming, Julie, author; Colorado State University, publisher (Colorado State University. Libraries, 2004)
An understanding of the transport of sediment in any river requires and understanding of the sizes of the sediment n the substrate and the sizes of transported sediment. Data in USGS records for the Rio Puerco near Bernardo show that 50% of the suspended load samples have at least 90% fines (<0.062 mm) and 90% of the samples have at least 77% or more fines. Samples from the river at a location above the gage show the surface material of the Rio Puerco has a median size of 0.0022 mm – very fine material. This layer is a few centimeters thick. Below this layer is substrate with a median size of 0.085 mm. Samples from the flood plain profile had a median size range of 0.007-0.20 with median in the range of 0.06. The flood plain and substrate samples have more sand than the suspended sediment size measurements imply. Another concern is the actual size of the sediment in transport. Data for the suspended sediment show significant differences in the sizes of the sediment measured using a dispersent compared to sizes with native water. To simulate this in the laboratory, very fine sediment (the surface material on the stream bed) was measured with and without dispersent. The size of the sediment measured with dispersent was 0.0022 mm compared to without dispersent median size of 0.01 mm. A similar test was done for one of the courser samples; the 'with dispersent' median size was 0.044 mm compared to 'without dispersent' median size of 0.050 mm. The analytical technique used in the laboratory determination of the particle sizes of suspended sediment and of the substrate must be part of the information reported in any study using grain size analysis.
Hydrology days 2004
AGU hydrology days 2004
24th annual AGU hydrology days was held at Colorado State University on March 10-12, 2004.